COOPERATIVE EVOLVEMENT THROUGH POLITICAL ERA / EPOCH: ALBANIANS CASE AND COMPARISONS - Sokoli, Olta; Doluschitz, Reiner (Economics of Agriculture, 2019)
The purpose of this paper is to analyse the structure and state of cooperatives in Albania as a country with a unique history, a post communism country on the development of cooperatives. It is important to understand the way cooperatives are perceived at higher levels. Information strongly influences the development of trust among farmers. Access to information and trust play an important role in the emerging stages of cooperatives. However, the development of cooperatives still remains a very delicate issue in Albania due to misleading of trust issues from the communism era. Cooperatives should not be a forbidden word in the Albanian vocabulary but instead should be considered as a normal and trusted topic at the governmental and organizational levels.